Flow Cytometry Analysis of Gingival and Periodontal Ligament Cells - Kuru, L.; Parkar, M.H.; Griffiths, G.S.; Newman, H.N.; Olsen, I. (Journal of dental research, 1998)
Gingival and periodontal ligament (PDL) fibroblasts are the major cellular components of periodontal soft connective tissues, but the precise differences between these cells are not yet known. In the present study, we have therefore examined the phenotypic and functional features of the cells obtained from gingival and PDL biopsy samples. Spindle-shaped cells characteristic of fibroblasts were the main cell type observed in vitro, although epithelial cells were also present in primary gingival cell cultures. Flow cytometry was used to measure the size and granularity of the cultured cells, and showed that the gingival fibroblasts were smaller and less granular compared with the PDL cells. The expression of certain key extracellular matrix (ECM) proteins, fibronectin, collagen type I, and tenascin was measured by flow cytometry. Analysis of the fluorescence profiles of these cultures showed that the majority of cells expressed fibronectin and that the average fluorescence intensity of this antigen in the PDL cells was higher than that in the gingival fibroblasts. Moreover, the fibronectin-positive PDL cells apparently comprised two subpopulations which expressed fibronectin at different levels, suggesting that the cells in the PDL cultures were functionally heterogeneous. The level of collagen type I was also found to be up-regulated in the PDL compared with the gingival cells and, as with fibronectin, was expressed at two different levels by subsets of the PDL cells. In contrast, tenascin was expressed at very similar levels by both the gingival fibroblasts and PDL cells. In addition, measurement of alkaline phosphatase, a marker enzyme for mineralized tissue-forming cells, showed that the PDL cells had higher activity than the gingival fibroblasts and that the alkaline phosphatase activity in the PDL cells was far more markedly up-regulated by dexamethasone. Our findings demonstrate that, despite their similar spindle-shaped appearance, fibroblasts derived from gingival and PDL tissues appear to display distinct functional activities which are likely to play a vital part in the maintenance of tissue integrity and regenerative processes.